An Overview of Myristica fragrans (Nutmeg) - Its benefits and adverse effects to Humans - Rashmi Gupta; Misbahuddin Azhar; Mohd Afsahul Kalam (Indian Journal of Integrative Medicine, 2022)
Myristica fragrans is an annual spice belonging to the family Myristicaceae. It has been cultivated throughout the world and used for food flavoring, essential oil applications and in traditional medicines. Mostly nutmeg contains terpenes and phenylpropenes. Chemical composition of these constituents varies due to different cultivation conditions. Nutmeg is considered as essential ingredient of numerous industrial applications ranging from food to cosmetics. Its pharmaceutical products are also important due to its antioxidant and antimicrobial properties. More uses and applications of nutmeg byproducts are continuously added. Nutmeg is used as a constituent in preparations of medicines such as for dysentery, flatulence, stomachache, nausea, vomiting, rheumatism, sciatica, malaria and early stages of leprosy.